The effects of auriculotherapy on pain and quality of life (Research, Society and Development, 2022)
Work is now one of the sources of illness due to several factors. Caring is necessary within companies so that illness does not interfere with the productivity and quality of life of its employees. Alternative therapies are applied to heal physical and mental pathologies, highlighting auriculotherapy, in improving pain and quality of life. The objective was to analyze the effects of auriculotherapy as an intervention to improve pain and quality of life in employees of a private educational institution. It is a field research, experimental, descriptive, with a quantitative approach. The sample consisted of 20 patients, of both genders, who reported musculoskeletal pain. For data collection, the visual analogue pain scale (VAS) and brief pain inventory (BDI) were applied. For statistical analysis, SPSS 22.0 software for Windows and Excel 2022 were used; a p< 5% was adopted. The analyzed domains that presented statistical significance were pain, mood, quality at work, sleep and appreciation of life, with p